AN INTERPERSONAL FUNCTION ANALYSIS OF JOKO WIDODO'S REMARKS IN G20 SESSION I - Desi Rahma Yuni Br.Sinulingga; Anna Theresia Simanjuntak; Nurlela Nurlela (Universitas Negeri Islam Sumatera Utara, 2023)
This research investigates the interpersonal function in Indonesian president Joko Widodo’s remarks in G20 session I. The objective is to find out the mood, speech role and modality in Indonesian president Joko Widodo’s remarks in G20 session I. This research use qualitative descriptive research method. The data of this research are clauses from the text entitle